Soft Sequences in Real Analysis - Abdullah hamad, Abdulsattar; Amarendra Babu, V.; ., . (International Journal of Engineering and Technology, 2018)
In This work is an attempt to present new class of limit soft sequence in the real analysis it is called ( limit inferior of soft sequence " and limit superior of soft sequence) respectively are introduced and given result an example with two new definitions and studied some of the properties of them are investigated.
Keywords: limit superior; limit inferior; soft sequences; Soft set; soft real numbers